Management of professional and specialized medical treatment in gunshot wounds of calvaria soft tissues - Danchin, Andriy; Polishchuk, Mykola; Danchin, George; Goncharuk, Oksana; Perekopayko, Yuri (Ukrainian Neurosurgical Journal, 2016)
Research objective. To analyze aspects of gunshot wounds of head soft tissues, their combination to brain injury and on this basis to develop tactics and the principles of assistance at different stages of medical care in compliance of the military medical doctrine. Materials and methods. On the basis analysis of 1214 combat injuries of neurosurgical profile gunshot wounds were in 434 (35.6%). Wounds of calvaria head soft tissues are diagnosed at 241 (55.4%), in 193 (44.6%) there were nonpenetrating and penetrating wounds with injury of brain. From 241 wounded 141 (58.5%) have finished treatment in the military medical hospital (MMH) (the second level of medical care) and in 100 (41.5%) wounded who had concussion, contusion of the brain and/or getting traumatic brain injury (TBI) were treated in neurosurgical departments. Results and Conclusions. It is revealed that in 141 (58.5%) gunshot wounds of head soft tissues are not followed with brain injury. These wounded are in group of the low risk development of intracranial complications (RDIC) and have finished treatment at the second level of medical care in the MMH. In 100 (41.5%) of wounded soft tissues were followed by symptoms of brain injury (concussion, contusion, hemorrhage). These patients had average and high RDIC, and have been evacuated on the 3rd level of medical care and have finished treatment in specialized neurosurgical departments (the 3 and 4 levels). Gunshot wounds of head soft tissues without neurologic symptomatology can be treated at stage of the qualified medical care - the 2nd level - in field hospitals. Gunshot wounds of head soft tissues (41.5%) are followed often by traumatizing brain with average and high risk development of intracranial complications and this group of patients is evacuated on the third level of medical care in specialized neurosurgical departments.